Pengaruh Modal Kerja dan Bahan Baku terhadap Pendapatan Pengusaha UMKM Handycraft di Kota Blitar - Yasin, Muhammad (Politeknik Negeri Padang, 2022)
This study aims to prove the effect of working capital and raw materials on the income of SMEs Handycraft entrepreneurs in Blitar City. This study uses quantitative methods with primary data. Primary data collection in this study used a questionnaire obtained from the respondents of SMEs Handycraft entrepreneurs in Blitar City. The analysis used in this study using multiple linear regression method. The results of this study prove that there is a significant effect partially or simultaneously between working capital and raw materials on the income of MSME Handycraft entrepreneurs in Blitar City. The working capital variable coefficient value obtained is 0.427 with a significance value of 0.000 <0.05, the raw material variable coefficient is 0.267 with a significant value of 0.000 <0.05. In simultaneous hypothesis testing, the calculated F test is 126,102, the F table is 3.21 and the significance value is 0.000 0.05, which means that working capital and raw materials simultaneously affect the income of MSME Handycraft entrepreneurs in Blitar City. Thus, it can be concluded that all hypotheses are accepted, which means that working capital and raw materials have an effect on the income of Handycraft MSME entrepreneurs in Blitar City.